Three‐dimensional networks containing rectangular Sr4 and Ba4 units: Synthesis, structure, bonding, and potential application for Ne gas separation. Issue 20 (4th September 2015) - Mandal, Subhajit; Pan, Sudip; Deb, Dibakar; Giri, Santanab; Duley, Soma; Radenković, Slavko; Cooper, David L.; Bultinck, Patrick; Anoop, Anakuthil; Bhattacharjee, Manish; Chattaraj, Pratim K.
<x xml:space="preserve">Abstract</x> New porous three‐dimensional metal‐organic frameworks are synthesized that contain infinite chains of Srn and Ban rectangles. Their structures are elucidated by means of spectroscopic techniques such as nuclear magnetic resonance and Fourier transform infrared, and the respective crystal structures are determined. The electronic structure of basic units of the crystals are computed using density functional theory at the B3LYP/6‐31G(d, p)/def2‐TZVP level, and the bonding and reactivity are analyzed using natural bond orbital analysis, the quantum theory of atoms in molecules, and conceptual density functional theory. The possibilities of noble gas (Ng) storage inside the crystal structures are explored through modeling a Ng atom inside the frozen geometry of the crystal. It was found that a neon atom can fit into a cavity in the Sr and Ba crystal structures whereas other Ngs (He, Ar, Kr) exhibit repulsive interactions with the crystal structure. Ab initio molecular dynamics simulations for up to 500 fs at 77 and 298 K suggest that the structures incorporating a neon atom are kinetically stable. © 2015 Wiley Periodicals, Inc.